Guerre Révolutionnaire, Counter-insurgency, and U.S. Domestic Extremism - Shane Praiswater; Quinn Hobbs (Journal for Deradicalization, 2023)
There is no shortage of academic literature regarding U.S. military veterans and their susceptibility to domestic extremist recruitment. However, this essay identifies a new potential culprit: military doctrine itself. Around 2006, amidst a deteriorating situation in Iraq, the U.S. military looked to history for innovative ideas on how to address a deteriorating counter-insurgency conflict. Unfortunately, they drew from several dubious historical examples, most notably, the documents crafted by French theorists during and after their 1954-1962 war in Algeria. We theorize that by heavily citing these French theorists without considering their conspiratorial underpinnings known as guerre révolutionnaire, the resulting product (FM 3-24, Counter-insurgency) inadvertently legitimized guerre révolutionnaire’s philosophies to U.S. military members. With the rise in domestic extremist groups correlating with FM 3-24’s publication, we examined whether guerre révolutionnaire’s concepts were present in modern extremist rhetoric. While it was not possible in this introductory study to establish a direct relationship between FM 3-24 and the rise in U.S. domestic extremism, we find that 1) guerre révolutionnaire’s tenets are present in U.S. extremist rhetoric, 2) there are subtle differences in rhetorical attitudes between veteran and non-veteran domestic extremists within their respective groups, and 3) previous concerns regarding the improper use of history for doctrine appear valid. Finally, we consider these results in the context of future studies regarding FM 3-24’s effects and the need for an interdisciplinary approach.